The analysis of National Health Accounts and financial communications network in Iran health insurance ecosystem - Rohaneh Rahimisadegh; Mohammad Hossein Mehrolhassani; Mohammad Jafari Sirizi; Somayeh Noori Hekmat (BMC, 2022)
Abstract Background One of the major reforms in the health system of any country is the financing reform. Network analysis as a practical method for investigating complex systems allows distinguishing prominent actors in the relation networks. Leading to the identification of the effective actors and key links between them, the analysis of financial networks helps policymakers to implement reformations by providing appropriate evidence. This study aimed to design and analyze the network of National Health Accounts (NHA) and the cost network in the Iran health insurance ecosystem. Methods The present study is a network analysis study based on the data from NHA, and both cost and referral rates that was conducted in 2021. Data, which was for the years 2014 to 2018 and related to NHA, was collected from the Statistical Center of Iran, and cost data and referral rates, which were both related to Basic Insurance Organizations (BIOs), were collected from statistical yearbooks. To analyze the network and identify the key actors, macro indicators, such as network size and density, and micro indicators, such as centrality indicators and the combined importance index, were used. Results In the financing of the health system in Iran, insurance organizations, as agents and sources of financing, do not have a very good position, so direct payments have become a key element in the network of NHA. Providing treatment-oriented services is quite prior. Regarded to health services, hospitals and outpatient services, such as pharmacies and physicians are the key elements of cost and referral rates respectively. Conclusion Consisting of several organizations with different insurance policies and being supervised under different ministries, Iran's health financing system lacks a coherent structure. It is suggested to create a coherent insurance system by creating a single governance system and paying more attention to health-oriented instead of treatment-oriented services. The health insurance ecosystem has become a health-oriented system to reduce the direct payments as well as cost management.